Ethical issues and social dilemmas in knowledge management : organizational innovation - Morais da Costa, Goncalo Jorge, 1979- (Hershey, PA : Information Science Reference, 2011)
'This book considers ethical issues and social dilemmas at two levels: the individual vs. individual and the individual vs. the collective, providing a thorough treatment of these facets and demonstrating the philosophical underpinnings of each dimension of knowledge management'--Provided by publisher.
Includes bibliographical references (p. 278-320) and index.
Keywords: Knowledge management; Information society -- Moral and ethical aspects; Organizational change